PRELIMINARY PALEOMAGNETIC INVESTIGATIONS ON PLEISTOCENE SEQUENCES IN LOMBARDY NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Paleomagnetic measurements have been carried out in continental sediments of Northern ltaly. The loess deposits of Copreno, the loess and paleosols of Cascina Lina and Barlassina, and the lacustrine sediments of Pontida all belong to the Brunhes Normal Polarity Epoch, in agreement with their previous chronostratigraphic classification. The lower lacustrine sediments of Bagaggera, previously attributed to the antepenultimate glaciation, belong to the Matuyama Reversed Polarity Epoch, whilee the overlying sandy-loamy sequence belongs to the Brunhes. At Leffe the entire sequence up to the top of the lacustrine sediments belongs to the Matuyama Epoch, being in such way older than previously admitted. These paleomagnetic results prove that the "ferretto" is a complex of paleosols of different age, ranging from Lower to Middle Pleistocene.
Keywords: Stratigraphy; Paleomagnetism; Pleistocene; Lombardy.